Determination Of The Efficient Production Plans For Al-Shaheed Public Company By Using Tatget Motad Model Under Risk And Uncertainty - العبدلي سعد نجم; حسين احمد وهيب (Journal of Economics and Administrative Sciences, 2011)
The research aims to derive the efficient industrial plans for Al – shaheed public company under risk by using Target MOTAD as a linear alternative model for the quadratic programming models. The results showed that there had been a sort of (trade- off) between risk and the expected gross margins. And if the studied company strives to get high gross margin, it should tolerate risk and vice versa. So the management of Al- Shaheed Company to be invited to apply the suitable procedures in the production process, in order to get efficient plans that improves it’s performance .